2018
DOI: 10.1111/jcpt.12765
|View full text |Cite
|
Sign up to set email alerts
|

l-selenomethionine supplementation in children and adolescents with autoimmune thyroiditis: A randomized double-blind placebo-controlled clinical trial

Abstract: Summary What is known and objective Although a beneficial effect of selenium (Se) administration has been proposed in adults with autoimmune thyroiditis (AT), there is a paucity of similar data in children and adolescents. The purpose of the study was to investigate whether administration of a high dose of organic Se (200 μg daily as l‐selenomethionine) has an effect on antithyroid antibody titres in children and adolescents with AT. Methods Seventy‐one (71) children and adolescents, with a mean age of 11.3 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
(154 reference statements)
0
14
0
1
Order By: Relevance
“…Se supplementation appears to reduce anti-Tg in the Se group compared with the placebo group. No significant difference in thyroid gland volume was observed [ 163 ]. A cohort of 102 subjects aged 15–78 years was randomized into three groups treated respectively with 200 μg/day sodium selenite, 500 mg vitamin C/day or a placebo over a 3-month period.…”
Section: Thyroid Diseasementioning
confidence: 99%
“…Se supplementation appears to reduce anti-Tg in the Se group compared with the placebo group. No significant difference in thyroid gland volume was observed [ 163 ]. A cohort of 102 subjects aged 15–78 years was randomized into three groups treated respectively with 200 μg/day sodium selenite, 500 mg vitamin C/day or a placebo over a 3-month period.…”
Section: Thyroid Diseasementioning
confidence: 99%
“…reported that if high-dose selenium was added, although anti-TPO and anti-Tg levels were reduced, the change did not differ significantly from that in the control group. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Попри велику кількість досліджень щодо ролі нестачі селену в розвитку тиреопатій та ефективності використання селену при лікуванні останніх [17,18] на сьогодні відсутні міжнародні клінічні настанови з призначення селеновмісних препаратів. Дискусія стосовно доцільності й ефективності їх використання триває в рамках міжнародних наукових конференцій.…”
Section: вступunclassified